Awareness of adverse drug reactions reporting among doctors in a tertiary care centre - V., Laila K.; T., Hemalatha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse drug reactions (ADR) are more commonly observed during treatment course in a substantial number of patients. Though we have a functioning pharmacovigilance programme in India, we have only fewer number of adverse drug reactions being reported indicating lack of awareness, the unsure attitude and reluctance in reporting adverse drug reactions. Methods: We conducted a cross sectional pretested questionnaire based study for a period of six months. 600 questionnaires were distributed. 521 responded back to the questionnaire of which 29.6% were interns, 56.8% were junior residents, 5.2% doctors were senior residents, and 8.4% were Assistant professors. Awareness on ADR reporting, ADRs encountered in practice, common causative drugs for ADR, and awareness on the functions of Pharmacovigilance programme of India were assessed. Results: 44.9% were not aware of the pharmacovigilance programme; 59.5% of the study population were not aware of the voluntary reporting of ADRs. 100% of the doctors who participated actively in the study responded that have not reported any ADR so far under pharmacovigilance programme of India. 88.1% of the doctors who participated in the study were willing to undergo a training on ADR reporting and pharmacovigilance. Conclusions: This study concludes that serious measures have to be taken to educate the doctors on ADR reporting and pharmacovigilance. By means of involving pharmacovigilance as a part of the undergraduate programme and by organising regular workshops, group discussion and continuous medical education, we can improve the awareness among doctors regarding ADR reporting and pharmacovigilance.